Research on assembly reliability control technology for computer numerical control machine tools. (January 2017) - Ran, Yan; Zhang, Genbao; Pang, Jihong
Nowadays, although more and more companies focus on improving the quality of computer numerical control machine tools, its reliability control still remains as an unsolved problem. Since assembly reliability control is very important in product reliability assurance in China, a new key assembly processes extraction method based on the integration of quality function deployment; failure mode, effects, and criticality analysis; and fuzzy theory for computer numerical control machine tools is proposed. Firstly, assembly faults and assembly reliability control flow of computer numerical control machine tools are studied. Secondly, quality function deployment; failure mode, effects, and criticality analysis; and fuzzy theory are integrated to build a scientific extraction model, by which the key assembly processes meeting both customer functional demands and failure data distribution can be extracted, also an example is given to illustrate the correctness and effectiveness of the method. Finally, the assembly reliability monitoring system is established based on key assembly processes to realize and simplify this method.